URGENCY OF INITIAL ASSESSMENT IN DETERMINING A MODEL OF EARLY CHILDHOOD LEARNING - Sofiyatul Anshoriyah; Supriati; Patmaria Krisnova Levryn; Nor Annisa; Nurmiah; Nurul Abidah; Masnah; Erna Budiarti (International Conferences on Early Childhood Education Proceedings, 2023)
This research aims to determine the process of child development through initial assessment in early childhood. The method used by researchers is a qualitative research method with a type of field research. Field research uses direct observation, interviews, or other data collection in the field, enabling researchers to gain an in-depth understanding of the phenomenon under study. To dig up information or get data by conducting interviews with teachers at institutions and supported by secondary data in the form of previous research articles that are relevant to the title and research objectives. The findings of this research are the process of child growth and development through which the initial assessment is carried out to identify children before entering school and at the beginning of the new school year. The instruments used are tests for height, weight, and then daily activities, then children are observed in various aspects and intelligence and carried out with tools and various tests.